Strategic spatial planning: Collective action and moments of opportunity - Newman, Peter (Taylor and Francis, 2008)
The theory and practice of strategic spatial planning makes a significant contribution to debates about contemporary European planning. Whilst its proponents describe a progressive style of governance and new territorial imaginations it is difficult to point to success on the ground. The paper argues that the normative conception of strategic spatial planning and focus on the failure of planners to live up to the ideal diverts attention from understanding the day-to-day work of planners and the ordinary politics of planning. We review some potentially helpful work in political sociology to develop framework that, rather than seeing planners failing to develop appropriate spatial and governance imaginations, may contribute to a better understanding of how planners pursue interests, attempt to manage the costs of collective action and assess institutional constraints and political opportunities.